(untitled) (Cadernos de Sociomuseologia, 2017)
This paper presented the thesis of museology master at Universidade Federal da Bahia. The text analyses questions of memory and oblivion in narratives of cultural representations, some encounters during in research, some investigative and theorical phases about museology, œuvres acquisition at Salões de Arte da Bahia and them documentation, the questions about œuvres ephemeral of Museu de Arte Moderna da Bahia, and the intangible and transitory that rise the perenniality in museums. Keywords: memory, museological documentation, salões de arte da Bahia, ephemeral œuvres.